Millennial-scale pulsebeat of glaciation in the Southern Alps of New Zealand. (15th September 2019) - Strand, Peter D.; Schaefer, Joerg M.; Putnam, Aaron E.; Denton, George H.; Barrell, David J.A.; Koffman, Tobias N.B.; Schwartz, Roseanne
Abstract: We undertook geomorphological mapping in conjunction with 10 Be surface-exposure dating in a previously unstudied sector of the left-lateral moraine sequence of the ice-age Pukaki glacier in the Southern Alps of New Zealand. The mapping and dating approach enabled the identification of six distinct moraine belts that were formed during maxima of glacier extent during the last glaciation. The chronology implies that ice recession occurred during Northern Hemisphere Heinrich stadials, while expansion occurred between Heinrich stadials. The ages of the moraine belts identified here are 44, 000 ± 1000 yrs; 41, 800 ± 1100 yrs; 36, 450 ± 940 yrs 26, 730 ± 740 yrs; 20, 030 ± 460 yrs; and 18, 000 ± 400 yrs. This moraine chronology is consistent with previous dating results from other sectors of the Pukaki moraine sequence, except that the c. 44, 000 yr old moraine belt has not previously been detected elsewhere in the Pukaki moraines. Collectively with previously published 10 Be chronologies from the Pukaki glacier, and the adjacent Ohau glacier valley, the results demonstrate that there were several millennial-scale episodes of ice advance to full-glacial extent, and subsequent ice recession, during Marine Isotope Stages 3 and 2. This millennial-scale pulsebeat of oscillations of the Pukaki and Ohau glaciers in sympathy with the North Atlantic Heinrich episodes is further emphasized by rapid ice recession in the Southern Alps early in the last glacial termination, coeval with the onset of Heinrich stadial 1 (HS 1) in the Northern Hemisphere. That this pattern is widespread in mid-latitudes of the Southern Hemisphere is highlighted by similar chronologies of glacier variation for Andean ice lobes in the Chilean Lake District of South America. Highlights: 10 Be chronology of the former Pukaki glacier, in the Mackenzie Basin of the Southern Alps of New Zealand. Heinrich stadial pulsebeat documented; glaciers expanded between Heinrich stadials and retreated during Heinrich stadials. Findings reveal millennial-scale teleconnections between polar hemispheres governing global climate.